What do they want from us? Reflections located to make the gaps more bearable between those who make the struggles and those who write them - Morales Martínez, Claudia Fernanda (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
10 years ago the Lencas communities of Honduras, organized in Copinh, began a blockade on the road to stop the access of the Agua Zarca Hydroelectric project that intended to privatize the Gualcarque River that crosses them. Attracted by their struggle, eight years later I went into their territory to dialogue with women who were part of the resistance in order to think together the relationship between the territory and the female bodies. The present work aims to present a series of reflections - subject personally and corporeal - around that research experience, to continue problematizing about the possibilities of producing knowledge that placed to the center the demands of those who resist the extractivist onslaught. It seeks to challenge our academic work with the question What do they want from us? and present some of the answers that come from the meeting with the indigenous women of that Central American country.